The Voices of Argumentation - Py Elichirigoity, Maria Teresinha (2010)
This article presents the analysis of a segment of a monograph written by a Law student at UCPel- RS, as a requirement for course conclusion. It shows the possibility of text interpretation based on Argumentative Semantic and Linguistics of Enunciation, as the analysis examines argumentation on the basis of polyphony present on the enunciates, and, at the same time, it recognizes different perspectives which generate argumentative movements in enunciates. The processes of this analysis articulate and integrate both Bakhtin’s and Ducrot’s theories.